The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/andr.12910
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcomes and predictors for successful sperm retrieval and pregnancy in 327 azoospermic men with a history of cryptorchidism who underwent microdissection testicular sperm extraction

Abstract: Background Although few studies have reported fertility outcomes, no study has reported risk factors that might predict sperm retrieval and pregnancy in azoospermic men with a history of cryptorchidism in a large series. Objectives To investigate fertility outcomes and predictors for successful sperm retrieval and pregnancy in azoospermic men with a history of cryptorchidism who underwent microdissection testicular sperm extraction (mTESE). Materials and methods This retrospective observational study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The situation is quite different for the predictive role of serum T on the chances of sperm retrieval, since studies in the field have reported conflicting results. We were able to individuate 14 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42] who clearly reported the relationship between serum T levels and sperm retrieval rates (SRR) (Table 1). Studies differed for study design, inclusion criteria, and patients' characteristics.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is quite different for the predictive role of serum T on the chances of sperm retrieval, since studies in the field have reported conflicting results. We were able to individuate 14 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42] who clearly reported the relationship between serum T levels and sperm retrieval rates (SRR) (Table 1). Studies differed for study design, inclusion criteria, and patients' characteristics.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
“…Seven studies included patients with subnormal presurgical T levels, and six of them [34,37,38,[40][41][42] provided the sperm retrieval rates in patients with low vs. normal T levels. We pooled these latter data to compute the resulting odds ratio (OR), using random-effects models to comply with the high heterogeneity in study design, as detected by I 2 and by Cochran's Q. Computations and forest plot were obtained using Review Manager (RevMan, Version 5.3.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
“…In the past few years, growing interest has been paid to predicting the sperm retrieval rate and pregnancy rates in azoospermic men, who underwent mTESE, but the results remain inconsistent. Çayan et al reported a study that NOA men with a history of cryptorchidism have high sperm retrieval rates with mTESE [ 9 ]. However, some studies have shown that there are no precise and noninvasive methods for predicting whether there are testicular spermatozoa in NOA patients before mTESE [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study utilizing an artificial neural network (ANN) to model the chance of SSR of 1026 men with NOA (770 training set, 256 test set) undergoing microTESE found that cryptorchidism was significant to the model [OR 2.29 (1.47–3.57), p < 0.0001] [ 8 ]. Sperm retrieval rates vary from 52.6% to 75% [ 12 , 13 , 14 , 15 ]. There is no consensus about the predictive ability of age at surgery, side (unilateral vs. bilateral) or testicular volume on SRR.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Ozan and coworkers evaluated 148 patients with NOA and history of cryptorchidism undergoing mTESE, and found that SSR did not vary with age at surgery (65.1% vs. 55.4% in patients undergoing orchidopexy before or after 10 years of age respectively) or side (62.9% vs. 59.3% in patients, with unilateral of bilateral cryptorchidism, respectively) [ 13 ]. Okada et al found that only testicular volume was predictive of SSR in a cohort of 36 formerly cryptorchid patients with NOA (OR 1.328, 95% CI 1.089–1619, p = 0.045) [ 14 ], while Cayan and collaborators evaluated a cohort of 327 azoospermic men with previous cryptorchidism, and found that SRR was higher in patients with total testicular volume > 13.75 mL (65.3% vs. 45.5%, p = 0.001), serum testosterone > 300.5 ng/dL (65.9% vs. 40.5%), serum FSH level > 17.25 mIU/mL (72.7% vs. 44.3%, p < 0.0001), and age at surgery < 9.5 years (70.8% vs. 42.1%, p < 0.0001) [ 15 ]. Well designed, multicentric studies are warranted to clarify the impact of age at surgery on the chances of SSR of formerly cryptorchid patients with NOA.…”
Section: Clinical Factorsmentioning
confidence: 99%